A unique macrolactam derivative via a [4+6]-cycloaddition from Streptomyces niveus. Issue 6 (15th March 2016) - Li, Liya; Cai, Yaping; Jiang, Yi; Liu, Jiang; Ma, Jian; Yuan, Chunhui; Mu, Yu; Han, Li; Huang, Xueshi
Graphical abstract: Abstract: One new macrolactam derivative, nivelactam (1 ) and one new polyenoic acid derivative, niveamide (2 ), along with two other known 20-atom macrolactams (3 and4 ) were isolated from the fermentation broth of Streptomyces niveus, which obtained from the forest soil in northeastern China. The structures of1 and2 were elucidated on the basis of HRESIMS, IR, and NMR spectroscopic data analyses. Compound1 was proposed as an intramolecular [4+6]-cycloaddition product of3 by S. niveus, and displayed moderate cytotoxic activity against a panel of human tumor cell lines in vitro, with IC50 values ranging from 3.76 ± 0.58 to 15.02 ± 2.81 μM.